The propensity of the Brazilian private sector to negotiate, join in and support trade and/or investment agreements with China that foster the attraction of Chinese Foreign Direct Investments (FDI) to Brazil - Zorovich, Marcelo Rocha e Silva (2020)
In the context of Sino-Brazilian relations, the central question and main hypothesis of this research aims to understand whether or not there is a propensity of the Brazilian private sector to negotiate, join in and support - trade and/or investment - agreements with China that may foster the attraction of Chinese Foreign Direct Investment (dependent variable) to Brazil. The private sector, in this case, is represented by C-Level executives and decision makers from multiple companies and sectors of the Brazilian economy. In addition to the central question, other related issues were addressed in order to contribute to this research agenda. As such, what should be the companies´ priorities in supporting such negotiations when comparing the Chinese influence to other political-economic powers (European Union, Mercosur, Pacific Alliance, and others), and in particular, with the United States? Which political and economic actors might be determinant to define the commercial or investment strategies that encourage the attraction of Chinese FDI to Brazil? How respondents would position themselves in terms of political-ideological preferences? Based upon the application of a Survey Experiment, with 312 valid answers obtained, the results were encouraging from the statistical point of view as well as innovative from the research design standpoint. Firstly, from the perspective of its variability, the Survey achieved its objective, as it did have respondents from 19 states of Brazil along with a variety of sectors and companies from different countries of origin, in addition to manifold revenue sizes. On the experiment results, respondents were randomly allocated to 3 (three) different groups (Group A: Control; Group B: Positive Treatment, and Group C: Negative Treatment), and all answered exactly the same questions, except for the last one, as it will be demonstrated throughout the text. Unlike what empirical research and the conventional wisdom suggest, the Brazilian private sector tends to be more favorable towards supporting the main hypothesis. Nevertheless, the negative treatment has a visible effect. Among these respondents, 42.1% declared themselves in favor of imposing barriers on China, a considerable value when compared to 23.9% in the control group. The difference between groups A (control) and C (negative) is statistically significant (p = 0.008), which brings up robust evidence that Clevel executives and decision makers (private sector) change their attitudes regarding China when they are reminded of the treatment that country gives to the environmental issues when relating them to FDI and trade.